Pemantauan Kelembapan dan Pengendalian Suhu Serta Pemberian Nutrisi Selada di Prototype Greenhouse dengan Nutrient Film Technique Berbasis IoT - Derafi, Ryan; Ullah, Aulia; Maria, Putut Son; Faizal, Ahmad (Universitas Budi Darma, 2024)
Nutrient Film Technique (NFT) is a hydroponic plant cultivation method in which plant roots grow in a shallow, particulated nutrient layer that allows plants to obtain water, nutrients and oxygen. In order to maintain a stable condition, kasturi farm hydroponic farmers experience problems in controlling and monitoring the condition of their plants, without having to sacrifice other activities. This research was carried out through a series of processes, starting from analyzing the needs, designing, and testing the design in providing nutrition, temperature control and monitoring the humidity of rockwool foam based on ESP 32. The hardware used are TDS (Total Dissolved Solids) Sensor, Ultrasonic Sensor, LDR (Light Dependent Resistor) Sensor, DHT 11 Sensor, Soil Sensor and DC Pump. The control used is ESP 32, and the application used is Blynk. The optimal control system in maintaining nutrients is 560 to 660 ppm and otherwise experiences a significant change of 1185 ppm. optimal temperature control with the highest temperature of 29.20 ËšC, and not using control will be more unstable. Rockwool humidity experienced an ideal stable increase of 50% - 56%. The average height of lettuce from the test results is about 22.07 cm with an average weight of 119.805 g. Measurement of lettuce plants indicated variations in fresh weight and height, with 3 prominent plants. The system effectively monitors and controls plant growth conditions, creating an optimal hydroponic environment. Based on the test results, the use of IoT technology in hydroponic NFT systems has proven to be very helpful for farmers in monitoring humidity, temperature and nutrients in real-time. Farmers can easily access plant condition information through remote devices, allowing farmers to immediately take necessary actions to maintain the health and productivity of hydroponic plants.